Nakadake sanroku kamaatosan sueki no seisan katei to sanchi d ōtei ni kansuru kōbutsugakuteki bunseki - Shinoto, Maria (Kenykū happyō yōshishū, 2014)
Übers. d. Hauptsacht.: Mineralogical analyses on the production process and provenance studies on Sue-ware from the Nakadake-sanroku kilns site